Integration of anaerobic biological and advanced chemical oxidation processes to facilitate biodegradation of fruit canning and winery wastewaters - Sigge, G. O. (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2005.